Biological characteristics of prospective plant Climacoptera lanata, growing in the South Kazakhstan (Experimental biology, 2015)
In this article presents the results of anatomical and morphological researches of the form of the families ChenopodiaceaeC.lanata encountered in the southern Kazakhstan. The paper presents the morphological features of plants and diagnosticcharacters. It is the length of their leaves, the size of the epidermis, palisade tissue parenchyma of aquifer, the diameter of the vascular bundles, the number and types of stomata per unit area, and the thickness of the stem to the radius of the primary cortex, the diameter of the cells of the central cylinder and epidermis. Installed localization biologically active substances:fatty acids - in the secretory cells of the sheet around the vascular bundles in the bark parenchyma cells and the xylem vessels stem; saponins in large quantities - in water-conducting tissues
Keywords: anatomy; morphology; atty acids; saponins; Climacoptera lanata